Exploring the interplay between female entrepreneurship and marriage: Insights through bibliometric analysis - Fard, Hajar Moayery; Jikidze, Ekaterine (Edelweiss Applied Science and Technology, 2024)
This study utilizes a bibliometric analysis to examine the intersection of marriage and female entrepreneurship and identify five key themes: the gender gap in entrepreneurship, rural women entrepreneurship, female entrepreneurial concerns, entrepreneurship-family structure, and cultural problems of women entrepreneurs. Conducting a strategic diagram shows that the “entrepreneurship-family structure” is extensively developed and central, while the “gender gap in entrepreneurship” and “female’s entrepreneurial concerns” show no internal development but provide foundational knowledge for the other themes. Conversely, “rural women's entrepreneurship” and “cultural problems of women’s entrepreneurs” are well developed in theory but lack practical application in all topics. Additionally, the study proposes a conceptual framework that illustrates how work-family conflict and role ambiguity influence the gender gap in entrepreneurship. Applying the developed framework helps reduce the gender gap in entrepreneurship.